Examining Students’ Perception of Using Google Classroom in English Online Learning - Subrata, Gede David (Jurnal Penelitian Mahasiswa Indonesia, 2022)
This study aimed to find the students’ perception on the use of Google classroom in English online learning during covid-19 pandemic which used a descriptive qualitative method research design. There were 102 students as the subject of this study. This study used open-ended questionnaire to collect the data. The collected data were analyzed by using the interactive data analysis. The result showed that in terms of perception in cognition aspect Google Classroom affect their cognition to positive direction. In affection aspect, Google Classroom brings positive emotional state to the students. In psychomotor aspect, students are negatively affected in the use of Google Classroom. The result found to support and in contrary to theories of advantages and disadvantages of Google Classroom.